Dampak Literasi Sekolah dalam Meningkatkan Minat Baca Siswa - Romadhoni, Desi Putri; Kusmawati, Heny (Journal of Elementary Education Research, 2023)
This research aims to determine the impact of a school literacy program in increasing reading interest in class IV students at MI Nurul Huda Bajomulyo Juwana. The theoretical benefit of this research is that it can develop the knowledge researched from a theoretical perspective, especially regarding the impact of school literacy programs in increasing fourth grade students' interest in reading at MI Nurul Huda Bajomulyo Juwana. For students, it is useful for increasing motivation and learning achievement. For teachers, it is useful to develop the quality of learning to be better. For institutions, these theoretical benefits are useful as a reference for improving school policies. Meanwhile, the practical benefits of this research are expected to provide benefits to educational practitioners. For students, it is useful to improve students' understanding of several subjects. For teachers, it is useful to increase teacher professionalism in carrying out teaching and learning activities. And for institutions, it is useful as an effort to improve the quality of teaching management. This type of research is field research with a descriptive qualitative approach. The research instrument is a human instrument (researcher himself). The data collection method uses interviews, documentation and observation. After the data is collected, data analysis is carried out using the data triangulation technique from Milles and Hubberman or by looking for data supporting the research objectives formulated by Data Reduction, Data Presentation, Conclusion Drawing and Verification, and Data Validity. The results of the data reduction are presented in the form of data displays using narrative descriptions, then the final step is to draw conclusions. The analysis used is data reduction, data presentation and conclusions. The results of this research are as follows: (1) In literacy activities at MI Nurul Huda, it is necessary to plan the activities first, then apply the methods that will be applied when the activities are carried out, then the school starts implementing the activities, and then evaluates the things that will be carried out. needs to be improved. (2) The positive impact of literacy activities is increasing students' interest in reading, students understanding the material they read, being able to create works for media, broadening their knowledge, making children read more fluently, the school has its own funds, class teachers can play an active role, support from students' parents. Meanwhile, negative impacts include laziness in students, students have difficulty concentrating, and students who are not fluent in reading will become increasingly backward.